What Motivates Leaders to Invest in Nation-Building? - Paola Giuliano; Bryony Reich; Alessandro Riboni (Institute of Labor Economics (IZA), 2022)
Why do some leaders invest in significant nation-building policies and others do not? Why does nation-building occur at certain junctures in time and not others? In our research, we investigate what motivates leaders to nation build. We argue that threats to their regime motivate rulers to invest in significant nation-building and that the type of threats that provoke nation-building have largely materialized since the 19th century.
Keywords: N0; P16; 330; nation-building; education; war